Characterization And Immunology Of Inflenza Virus Type A Isolated From Duck In Kerala - Mini M (Department of microbiology, College of veterinary and animal sciences, 1988)
Ducks are generally regarded as resistant to influenza virus infection. During the early halves of 1985 and 1987 influenza A viruses were isolated from cases of respiratory disease causing 15 to 20 percent mortality in two to six week-old ducklings at Government Duck Farm, Niranam. Four strains of the virus (A/duck/India /1/85 (H9N2)-CDN, A/duck/India /2/87 (H3N?) –DT3; A/duck/India /7/87 (H3N2)-T19 and A/duck/India /14/87 (H9N?-lgl isolated from these out breaks were studied in detail with particular reference to their characteristics, Pathogenicity and immunogenicity.